2015
DOI: 10.3109/01443615.2015.1030608
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hypertension and plasma allantoin, uric acid, xanthine oxidase activity and nitrite, and their predictive capacity in severe preeclampsia

Abstract: It is controversial that uric acid (UA) levels are related to the severity of hypertension in preeclampsia (PE). Our aim in this study was to determine whether UA, xanthine oxidase activity (XOA), allantoin and nitrite levels are related to arterial blood pressure (BP) in PE. We formed a control group (n = 20) and a PE group (n = 20) for the study. Their BPs and plasma UA, XOA, allantoin and nitrite levels were measured. The values from the control and PE pregnant women were assessed via a Wilcoxon matched-pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…These correlations coincided with Elmas et al (25) who found serum levels of UA, XOA and allantoin levels showed high correlations with blood pressure in cases of PE.…”
Section: Discussion:-supporting
confidence: 70%
See 3 more Smart Citations
“…These correlations coincided with Elmas et al (25) who found serum levels of UA, XOA and allantoin levels showed high correlations with blood pressure in cases of PE.…”
Section: Discussion:-supporting
confidence: 70%
“…In line with this finding, considering persistently elevated or progressively elevating liver enzymes as a manifestation of severe PE (33) , Atiba et al (25,34) reported positive correlation between serum MDA levels and serum levels of both AST and ALT and concluded that elevated liver enzymes seen in PE women may be due to free radical injury to the liver.…”
Section: Discussion:-mentioning
confidence: 60%
See 2 more Smart Citations
“…Decreased placental perfusion due to impaired remodeling of spiral arteries might result in hypoxia [139]. UA level showed high correlation with BP in cases of PE [140]. In pregnant ladies suffering PE, serum tumor necrosis factor α (TNFα) and ICAM1 were significantly higher than control or hypertensive pregnant ladies.…”
Section: Uric Acid and The Kidneymentioning
confidence: 99%